2000
DOI: 10.26719/2000.6.2-3.391
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between normal glucose-6-phosphate dehydrogenase level and haematological parameters

Abstract: The study involved 143 individuals and aimed to correlate normal glucose-6-phosphate dehydrogenase [G6PD]level with haematological parameters. A statistically significant negative correlation was found between G6PD level and haemoglobin, packed cell volume, red blood cell count, mean corpuscular haemoglobin and mean corpuscular volume. A statistically significant positive correlation was found between G6PD level and white blood cell count and reticulocyte count, but no significant correlation was found between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is thus concluded that qualitative tests and hospital studies very poorly demonstrate the actual position of this serious threat because mainly diseased people visit hospitals and they do not represent the whole population for prevalence, thus detailed investigations in various ethnic groups at a larger level must be carried out. In Asian countries, its prevalence has been reported in Indonesia, Thailand, Malaysia, Bangladesh, [20][21][26][27][28][29][30] Pakistan and China.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus concluded that qualitative tests and hospital studies very poorly demonstrate the actual position of this serious threat because mainly diseased people visit hospitals and they do not represent the whole population for prevalence, thus detailed investigations in various ethnic groups at a larger level must be carried out. In Asian countries, its prevalence has been reported in Indonesia, Thailand, Malaysia, Bangladesh, [20][21][26][27][28][29][30] Pakistan and China.…”
Section: Discussionmentioning
confidence: 99%
“…We do not have genotype information available for the majority of our patients in this study, which may provide a better predictor of risk of hemolysis than a single measurement of G6PD activity. 9 As G6PD levels can be elevated in the setting of reticulocytosis 10 and/or elevated leukocyte counts, 11 further correlation with genotype and G6PD assay level may provide important clinical insights to predict the risk of clinically significant hemolysis. Indeed, 3 patients with anemia in this study were not re-tested at a later date within our institution and so their levels may have been artificially elevated.…”
Section: Discussionmentioning
confidence: 99%